2009
DOI: 10.1021/jp903845e
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Zeta Potential in Semiconcentrated Dispersions of Titania in Polar Organic Solvents

Abstract: The electrokinetic potential of commercial titania powder (chiefly anatase) in its 1−10 mass % dispersions in water, lower aliphatic alcohols, and dimethyl sulfoxide (DMSO) is positive, and rather insensitive to the nature of the solvent. The sign of the electrokinetic potential can be reversed to negative by addition of phosphoric acid, or of combination of phosphoric acid with triethylamine or with alkali hydroxide. The critical concentration of surface-active compounds, which induces a sign reversal, depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
4
24
1
Order By: Relevance
“…During this sol-gel transition, N -octylamine plays several roles: (1) it acts as a basic catalyst of the sol-gel reaction [ 21 ]; (2) it promotes formation of a particulated silica mesostructure, preventing cracking [ 21 ] and (3) it adjusts the pH of the media to values above the isoelectric point of TiO 2 NPs, giving rise to negative charges in these NPs that produce mutual repulsive forces. Thus, TiO 2 aggregation is avoided during sol-gel transition and, consequently, a homogeneous gel is produced [ 21 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…During this sol-gel transition, N -octylamine plays several roles: (1) it acts as a basic catalyst of the sol-gel reaction [ 21 ]; (2) it promotes formation of a particulated silica mesostructure, preventing cracking [ 21 ] and (3) it adjusts the pH of the media to values above the isoelectric point of TiO 2 NPs, giving rise to negative charges in these NPs that produce mutual repulsive forces. Thus, TiO 2 aggregation is avoided during sol-gel transition and, consequently, a homogeneous gel is produced [ 21 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present approach is different from many other publications, in which the f potentials are plotted as the function of the molar concentration of solute. The advantages of our approach in studies carried out at various solid-to-liquid ratios have been discussed in detail elsewhere [12,13]. Namely, the course of electrokinetic curves plotted as the function of the molar concentration strongly depends on the solid-to-liquid ratio, while in the coordinates used in the present paper, the electrokinetic curves obtained at various solid-to-liquid ratios are more consistent, and often, one master curve is observed over a broad range of solid-to-liquid ratios.…”
Section: Methodsmentioning
confidence: 99%
“…The element mapping images indicated that the cells cohered with each other via the silica phase in the aggregates. Moreover, the surface potential of each silica-incorporated cyanobacteria was reduced to −3 mV (SI Figure S2), and the lower electrostatic repulsion favored particle agglomeration. Because of the relatively high specific gravity (2.2 g/cm 3 ) of silica, the aggregates sank to the beaker bottom within 20 min (Figure D) in our experiments. However, the native cyanobacteria could remain suspended in water uniformly and stably (SI Figure S8).…”
Section: Results and Discussionmentioning
confidence: 82%